2015
DOI: 10.2337/db15-0272
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterization of MIP-CreERT1Lphi Mice With Transgene-Driven Islet Expression of Human Growth Hormone

Abstract: There is growing concern over confounding artifacts associated with β-cell–specific Cre-recombinase transgenic models, raising questions about their general usefulness in research. The inducible β-cell–specific transgenic (MIP-CreERT1Lphi) mouse was designed to circumvent many of these issues, and we investigated whether this tool effectively addressed concerns of ectopic expression and disruption of glucose metabolism. Recombinase activity was absent from the central nervous system using a reporter line and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
106
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(122 citation statements)
references
References 41 publications
11
106
0
5
Order By: Relevance
“…Interestingly, Oropeza et al (12) did not observe impaired glucose-stimulated insulin secretion and decreased GLUT2 levels as was shown before in the Pdx1-Cre model that also expresses hGH in islets (17). This suggests that these impairments are independent of hGH bioactivity.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Interestingly, Oropeza et al (12) did not observe impaired glucose-stimulated insulin secretion and decreased GLUT2 levels as was shown before in the Pdx1-Cre model that also expresses hGH in islets (17). This suggests that these impairments are independent of hGH bioactivity.…”
supporting
confidence: 52%
“…In addition, no adverse effects on glucose tolerance and glucose-stimulated Ca 2+ release were observed (19). However, Oropeza et al (12) provide a more extensive and detailed analysis of this mouse model. First, strong evidence is provided using higher resolution techniques and the mT/mG reporter line (20) that Cre activity is indeed exclusively found in b-cells and not in hypothalamic or hindbrain nuclei, as was reported before in other strains (7,8).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The MIP-CCK mice are therefore a model of ␤-cell-derived CCK overexpression, with ␤-cell CCK expression levels similar to those found in obese models. Recently, several reports have described expression of human growth hormone (hGH) protein from the hGH minigene, which is included in many murine transgene constructs to increase transgene expression (3,6,45). As our MIP-CCK construct contained the same hGH minigene, we needed to examine whether we also had expression of hGH protein.…”
Section: E821mentioning
confidence: 99%
“…Recently it has been reported that glucose tolerance is altered in MIP-CreERT mice under certain conditions. 41 In pooling female littermate control data, it was determined that MIP-CreERT mice did not differ from wildtype or PKA-CaR littermates in either body weight (P > 0.05, 1-way ANOVA) or in glucose tolerance (P > 0.05, 2-way ANOVA). The PKA-CaR allele was induced by administering tamoxifen at 10 weeks of age by injecting 3 mg i.p.…”
Section: Animalsmentioning
confidence: 99%